Melon Waste Ecoenzyme: An Eco-friendly Liquid Organic Fertilizer for Vegetative Growth of Melon (Cucumis melo L. var. Merlin) - Ulmillah, Aulia; Satitiningrum, Yuni; Agilliana, Intan (3BIO: Journal of Biological Science, Technology and Management, 2025)
The utilization of melon plant waste, such as fruit peels, leaves, and stems, can be done by processing it into eco-enzyme, which is then used as liquid organic fertilizer. This study aims to assess the effect of eco-enzyme on the vegetative growth of melon plants. The randomized block design (RBD) method was used with seven treatments and four replications, including P0 (negative control), P1 (10 mL/L), P2 (20 mL/L), P3 (30 mL/L), P4 (40 mL/L), P5 (50 mL/L), and P6 (positive control). Observations were made every 7 days for 30 days, with parameters including plant height, leaf area, number of leaves, plant fresh weight, and root fresh weight. Data analysis was conducted using one-way ANOVA and Duncan’s test. The results showed that treatment P5 (50 mL/L) produced the best results with a plant height of 36.68 cm, leaf area of 137.33 cm², 11.56 leaves, plant fresh weight of 67.1 g, and root fresh weight of 2.24 g. These results were not significantly different from the positive control (P6). Thus, eco-enzyme had a significant effect on the vegetative growth of melon plants.